An Image of a woman in the Kurdish Short Story in Bahdinan that is written by Men - Nafeesa Ismail Haji (Zanco Journal of Human Sciences, 2025)
This study explores the portrayal of women in Kurdish short stories in Bahdinan since the year 2000. Women, despite their diverse roles in life, face numerous challenges, problems, and injustices in male-dominated societies. Literature serves as a valuable platform for expressing women's issues and suffering, providing means for their voices to be heard. Some argue that a female writer may better articulate her experiences, emotions, and voice compared to a male writer, when he writes about them. However, given the limited presence of women writers in the literary genre of short stories in Bahdinan region, this study focusses on the image of women in texts written by men. The research questions of the study are as follows: What image of women do Kurdish writers portray? Is it the same familiar, stereotypical depiction prevalent in Kurdish society, or do they transcend this image to introduce a more modern representation suited to the current era? Considering women as 'the other' in relation to the male writer, the study aims to examine how this 'other' is portrayed in narratives. Additionally, the study seeks to explore whether Kurdish writers have made efforts to articulate women's suffering and amplify their voices. Upon examining the research questions and objectives of the study, it becomes evident that the majority of the texts are written in the third-person omniscient point of view. This means that, although the focus is on the portrayal and characterization of women, the authors do not narrate from a first-person perspective nor place themselves in the position of the woman. The image of the oppressed woman—powerless and often subjected to death—dominates the stories. Most narratives present the familiar societal depiction of women. The portrayal of women as equals to men is rare.